2021
DOI: 10.1016/j.bj.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Vertical dimension of occlusion related to mandibular movement during swallowing

Abstract: Background Increasing the vertical dimension of occlusion (VDO) is a common procedure in complicated prosthodontic treatment. The swallowing technique had been verified as a functional method to determine the VDO. The purpose of this study was to investigate the association between increasing VDO and mandibular movement during swallowing. Methods 26 females and 14 males were enrolled (age range: 21 to 30 year-old). Under different increased VDO (3, 5, and 8 mm), the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, VDO and tongue pressure are related (9,15) and affect mastication (9 -12) and swallowing (7,15,17) .…”
Section: Discussionmentioning
confidence: 99%
“…However, VDO and tongue pressure are related (9,15) and affect mastication (9 -12) and swallowing (7,15,17) .…”
Section: Discussionmentioning
confidence: 99%
“…A study observed that the increase in VDO could change the extent of mandibular trajectory during swallowing only if the increase was more than 3 mm. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…examine in their study the relation between a gradual artificial VDO increase and mandibular movement during swallowing in healthy subjects. Indeed, they find a positive correlation between VDO and mandibular movement in the lateral direction, but also point out that natural physical adaptation is likely to temper most initial discomfort [ 42 ].…”
Section: Also In This Issuementioning
confidence: 99%